The relationship between transformation leadership, job satisfaction and employee motivation in the tourism industry - Nguyen Quang Vinh; Luc Manh Hien; Do Quang Hung (Administrative Sciences, 2022)
The objective of this study is to investigate the relationship between transformation leadership, job satisfaction, and employee motivation in the Vietnam tourism industry (VTI). In the study, data were collected from 207 respondents from different organizations related to the tourism industry, then partial least squares structural equation modeling (PLS-SEM) was employed for the analysis. The findings indicate that the paths between inspirational communication, personal recognition, supportive leadership, vision, and job satisfaction are highly significant. However, the intellectual stimulation does not positively affect job satisfaction. In addition, the path of job satisfaction and employee motivation is significant. This research also shows that only supportive leadership has a direct positive effect on employee motivation. The findings can be used as reference for tourism company managers to consult and improve their knowledge, skills, and leadership qualities.
Keywords: 350; employee motivation; job satisfaction; transformation leadership; Vietnam tourism industry